Responding to Change: Girl Scouts, Race, and the Feminist Movement - (:unkn) unknown (My University, 2018)
The purpose of the Girl Scouts of the United States of America (GSUSA) is to teach girls to be giving, self-sufficient, and independent in their homes and communities through volunteer work and earning merit badges. Open to all girls since its inception, the GSUSA offers Girl Scouts training in both gender-conforming and nontraditional vocations. However, during the first half of the twentieth century, segregation and domesticity was emphasized in American society. The organization began to focus less on careers, independence, and racial inclusion to preparing predominately white girls to be good wives and mothers. As Black Power and women’s liberation gained momentum in the early 1970s, the GSUSA decided to increase its racial diversity and move in a more feminist direction by nominating Betty Friedan to the National Board of Directors and endorsing the Equal Rights Amendment. Despite the anti-feminist backlash from the membership, the GSUSA continued to support women’s liberation.
Keywords: African American; Betty Friedan; Equal Rights Amentment; feminism; Girl Scouts; women's rights movement